Desorption of water cluster ions from the surface of solid rare gases - Tachibana, T.; Miura, T.; Arakawa, I. (Физика низких температур, 2006)
Electron or photon irradiation on H₂O adsorbed on the surface of rare gas solids induces the desorption of protonated water clusters, (H₂O)nH⁺. The yield and the size n distribution of cluster ions depend on the coverage, the deposition temperature of water and the thickness of a rare gas film. These results indicate that the (H₂O)nH⁺ ions are originated from the isolated water cluster and most important factor determining the size n distribution of desorbed (H₂O)nH⁺ is the sizes of water islands on rare gas solid. The measurement of kinetic energy distributions indicated that the desorbing energy of clusters depend on the rare gas species of the substrates and the cluster size. It is suggested that the (H₂O)nH⁺ desorption is due to Coulomb repulsion between the ionic water cluster and the rare gas ion.